2021
DOI: 10.9734/cjast/2021/v40i931353
|View full text |Cite
|
Sign up to set email alerts
|

Application of Phosphorus and Calcium to Improve Physiological Response of Groundnut (Arachis hypogaea L.)

Abstract: Genotype, environment and agronomic practices are key determinants of crop   growth and productivity which are important to provide food, feed, raw materials and income to small holder farmers in Africa. The study was conducted at Crop museum, Sokoine University of Agriculture, Morogoro, Tanzania to investigate physiological response of groundnut to calcium and phosphorus nutrition among three improved groundnut genotypes Mangaka (G1), Masasi (G2) and Pendo (G3) with three levels of phosphorus and at calcium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…It's also important for respiration, cell division and cell growth things that are integral to the development of the plant and its fruit. Similar findings were made by Nyuma [39] who also found that application of P significantly decreased the number of empty pods per plant.…”
Section: Number Of Pods and Empty Pods Per Plant And Number Of Kernel...supporting
confidence: 87%
See 1 more Smart Citation
“…It's also important for respiration, cell division and cell growth things that are integral to the development of the plant and its fruit. Similar findings were made by Nyuma [39] who also found that application of P significantly decreased the number of empty pods per plant.…”
Section: Number Of Pods and Empty Pods Per Plant And Number Of Kernel...supporting
confidence: 87%
“…This was a clear indication that phosphorus application at sowing helped to increase the number of kernels per pod in groundnut production. Similar studies have shown that the number of kernels per pod was increased by P application at sowing [39]. Drammeh [40] also made similar findings and stated that when phosphorus was applied to groundnuts at sowing, it resulted to increase growth ancillaries which were due to cell division and rapid development of meristematic tissues which resulted in a greater plant height.…”
Section: Number Of Pods and Empty Pods Per Plant And Number Of Kernel...mentioning
confidence: 58%